Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/biomedicines9040351
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Human Cytomegalovirus Infection on Immunity to Ovarian Tumours and Cancer Progression

Abstract: Ovarian cancer (OC) is one of the most common, and life-threatening gynaecological cancer affecting females. Almost 75% of all OC cases are diagnosed at late stages, where the 5-year survival rate is less than 30%. The aetiology of the disease is still unclear, and there are currently no screening method nor effective treatment strategies for the advanced disease. A growing body of evidence shows that human cytomegalovirus (HCMV) infecting more than 50% of the world population, may play a role in inducing carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 98 publications
1
21
0
2
Order By: Relevance
“…The anti-inflammatory cytokine, IL-10 can paradoxically induce STAT-3 activation ( 34 ), which also leads to induction of tumor cell proliferation ( 35 37 ). Interestingly, the CMV-derived IL-10 also promotes the proliferation and migration of cancer cells ( 38 , 39 ), linking chronic infections such as CMV to cancer formation ( 40 ).…”
Section: Cytokines In Tumor Growthmentioning
confidence: 99%
“…The anti-inflammatory cytokine, IL-10 can paradoxically induce STAT-3 activation ( 34 ), which also leads to induction of tumor cell proliferation ( 35 37 ). Interestingly, the CMV-derived IL-10 also promotes the proliferation and migration of cancer cells ( 38 , 39 ), linking chronic infections such as CMV to cancer formation ( 40 ).…”
Section: Cytokines In Tumor Growthmentioning
confidence: 99%
“…In a previous study, lipid raft microdomains were shown to be essential components of phagolysosomal macrophage membranes and to play an essential role in antifungal immunity (Schmidt et al, 2020). Moreover, human cytomegalovirus infection was shown to potentially impact immunity (Cox et al, 2021). Thus, our subsequent research will be performed using macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of HCMV infection in late inflammatory complications highlights its potential association with chronic diseases, such as atherosclerosis, chronic rejection following solid-organ transplantation, and malignancies (24). Recent investigations have reported the prevalence of HCMV infection in tumoral tissues of malignancies such as malignant glioma, breast and colon cancer, negative Hodgkin's disease, Epstein-Barr virus (EBV), liver cancer, cervical cancer, and prostatic carcinoma (1,25,26). Despite the fact that HCMV is not yet included in the oncogenic viruses list, its possible contribution in carcinogenesis as initiator or promoter is significantly reported suggesting that HCMV and tumors express a symbiotic relationship (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…HCMV or human herpesvirus 5 (HHV-5) has co-evolved with mammalian hosts over millennia infecting almost 83% of the world’s population, impending 100% in developing countries ( 1 ). After initial infection, HCMV can establish lifelong persistence within its corresponding host as well as possessing the reactivation potential; viral persistence depends on composite interactions among various viral and host determinants.…”
Section: Introductionmentioning
confidence: 99%